Composite glass stone and preparation method thereof

By introducing sealing tape and light source into composite stone and removing moisture and bubbles during bonding, the problem of water absorption of existing composite stones is solved, and the bonding fastness and decorative aesthetics of composite stones are improved. , overcome the problems of scarcity and high cost of natural stone resources.

CN109501508BActive Publication Date: 2024-12-13WUXI CHENGYI STONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201811566810.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2018-12-20
Publication Date
2024-12-13
Estimated Expiration
2038-12-20

AI Technical Summary

Technical Problem

The viscosity of existing composite stones decreases after absorbing water, resulting in degumming and cracking, and there are many bubbles in the laminate layer, poor decorativeness, and scarce natural stone resources and high costs.

Method used

Compound glass stone composed of stone, sealing tape and light source, and the outer frame is set on the outer periphery of the stone part and pretreated during the bonding process to remove moisture and bubbles. Adhesive layers such as GS film and EVA film are used. and sealing materials such as aviation-grade waterproof and weather-resistant hot melt tape to ensure bonding fastness and aesthetics.

Benefits of technology

Effectively prevent the adhesive layer and stone layer from decreasing after absorbing water, enhance the bonding fastness and decorative aesthetics of composite stones, and ensure the stability and aesthetic effect of large-sized composite stones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN109501508B_ABST
    Figure CN109501508B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite glass stone and a preparation method thereof, wherein the composite glass stone is composed of a stone part and an outer frame arranged on the periphery of the stone part, a sealing belt is arranged at the section of the stone part, and a light source is arranged inside the outer frame. The composite glass stone of the present invention is provided with a sealing belt at the section, which can effectively prevent the viscosity of the adhesive layer from decreasing after absorbing water; the provision of the outer frame and the light source is helpful for the image display of laser engraved tempered glass; in the process of bonding the composite glass stone, the present invention removes moisture and bubbles in the glass, adhesive layer, stone and polyester mesh through pretreatment, which can ensure that the composite glass stone is bonded more firmly; and then through bonding and shaping, the overflow glue generated during bonding is removed, and the bubbles in the adhesive layer and the sealing belt are further removed, so as to ensure the bonding strength and decorative beauty of the composite stone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of decorative composite stone materials, and in particular to a composite glass stone material and a preparation method thereof. Background technology:

[0002] Stone is widely used as a decorative material, but the following problems still exist during its use: the color and pattern of stone are relatively simple, and the decorative beauty is insufficient; the surface of stone is very easy to be weathered, the strength is insufficient, and it is easy to break when made into large-sized decorative panels; in addition, natural stone resources are relatively scarce, and the cost of making decorative materials is relatively high; therefore, people have developed composite stones with glass and stone laminated together, but on the one hand, the viscosity of the adhesive layer and the stone layer of the existing composite stone is significantly reduced after absorbing water, which in turn affects the viscosity between the glass and the stone, causing debonding and cracking, thereby losing its decorative effect; on the other hand, the existing composite stone often has more bubbles in the laminated layer and has poor decorative effect.

[0003] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0004] The object of the present invention is to provide a composite glass stone material and a preparation method thereof, so as to overcome the defects in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides a composite glass stone, which consists of a stone part and an outer frame arranged outside the stone part, a sealing belt is arranged at the cross section of the stone part, and a light source is arranged in the outer frame.

[0006] The stone part comprises stone, adhesive layer, glass, adhesive layer and stone from top to bottom, the thickness of the stone is 1-5 mm, the adhesive layer is GS film, EVA film, PVB film, TPU film or SGP film, the thickness of the adhesive layer is 20-100 μm, the glass is laser engraved and dotted float glass, laser engraved and dotted tempered glass, laser engraved and dotted PMMA board, laser engraved and dotted PC board, laser engraved and dotted PETG board or laser engraved and dotted PET board, and the thickness of the glass is 1-25 mm.

[0007] The stone part comprises glass, an adhesive layer and stone from top to bottom, the thickness of the stone is 1-5 mm, the adhesive layer is GS film, EVA film, PVB film, TPU film or SGP film, the thickness of the adhesive layer is 20-100 μm, the glass is laser engraved and dotted float glass, laser engraved and dotted tempered glass, laser engraved and dotted PMMA board, laser engraved and dotted PC board, laser engraved and dotted PETG board or laser engraved and dotted PET board, and the thickness of the glass is 1-25 mm.

[0008] The stone part is glass, adhesive layer, stone, adhesive layer and glass from top to bottom, the thickness of the stone is 1-5mm, the adhesive layer is GS film, EVA film, PVB film, TPU film or SGP film, the thickness of the adhesive layer is 20-100μm, the glass is laser inner engraving and dotting float glass, laser inner engraving and dotting tempered glass, laser inner engraving and dotting PMMA board, laser inner engraving and dotting PC board, laser inner engraving and dotting PETG board, laser inner engraving and dotting PET board, float glass, tempered glass, PMMA board, PC board, PETG board, PET board, and the thickness of the glass is 1-25mm.

[0009] The two adhesive layers form a closed loop.

[0010] The stone part comprises glass, adhesive layer, metal-coated polyester mesh, adhesive layer and glass from top to bottom, the polyester mesh has a thickness of 1-5 mm, the adhesive layer is GS film, EVA film, PVB film, TPU film or SGP film, the adhesive layer has a thickness of 20-100 μm, the glass is laser engraved and dotted float glass, laser engraved and dotted tempered glass, laser engraved and dotted PMMA board, laser engraved and dotted PC board, laser engraved and dotted PETG board, laser engraved and dotted PET board, float glass, tempered glass, PMMA board, PC board, PETG board, PET board, and the glass has a thickness of 1-25 mm.

[0011] The sealing tape is aviation-grade waterproof and weather-resistant GS hot-melt tape, PEN hot-melt tape, PES hot-melt tape, PA hot-melt tape, TPU hot-melt tape or PO hot-melt tape, and the thickness of the sealing tape is 5 to 50 μm.

[0012] The outer frame is a stainless steel frame, an aluminum profile frame, a PVC frame or an ABS frame.

[0013] The light source is an LED light source.

[0014] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0015] 1) Stone preparation: Cut and grind the base stone into 1-5mm thickness and 3000mm*2000mm size stone; can be cut to any size;

[0016] 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass, stone and metal-coated polyester mesh to remove dirt and impurities on the surface;

[0017] 3) Pretreatment: Place the glass, adhesive layer, stone, and metal-coated polyester mesh in a constant temperature and humidity environment for 48 to 72 hours, wherein the ambient temperature is 16 to 20° C. and the ambient humidity is 6% to 12%;

[0018] 4) Stone bonding: Place the pre-treated glass, adhesive layer, stone and metal-coated polyester mesh according to the predetermined layer structure, and place sealing tapes on the surrounding sections. Evacuate the bonding chamber to 1 atmosphere, and heat the bonding chamber to 135-150°C for 50-70 minutes before taking out the composite glass stone semi-finished product.

[0019] 5) Post-pasting shaping: Use a mixed solvent of alcohol and acetone to wipe off the adhesive layer and residual adhesive of the sealing tape that overflowed from the composite glass stone semi-finished product during the pasting, and reheat the composite glass stone semi-finished product at a temperature of 120-150°C for 20-30 minutes;

[0020] 6) Installation of outer frame: install the light source in the outer frame, and then install the outer frame on the outside of the sealing belt to obtain a composite glass stone finished product.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The composite glass stone of the present invention is provided with a sealing tape at the cross section, which can effectively prevent the adhesive layer, the stone layer and the metal-coated polyester mesh layer from decreasing in viscosity after absorbing water; the provision of an outer frame and a light source is helpful for the image display of laser-engraved tempered glass; in the process of bonding the composite glass stone, the present invention removes moisture and bubbles in the glass, the adhesive layer, the stone and the metal-coated polyester mesh through pretreatment, which can ensure that the composite glass stone is bonded more firmly; and then through bonding and shaping, the overflow glue generated during bonding is removed, and the bubbles in the adhesive layer and the sealing tape are further removed, so as to ensure the bonding strength and decorative aesthetics of the composite stone. Description of the drawings:

[0023] Figure 1 It is a structural schematic diagram of embodiment 1 of the present invention;

[0024] Figure 2 This is a schematic diagram of the structure of Embodiment 2 of the present invention;

[0025] Figure 3 This is a schematic diagram of the structure of Embodiment 3 of the present invention;

[0026] Figure 4 It is a structural schematic diagram of embodiment 4 of the present invention;

[0027] Figure 5 This is a schematic diagram of the structure of Embodiment 5 of the present invention;

[0028] Figure numerals: 1 - stone part, 11 - stone, 12 - adhesive layer, 13 - glass, 14 - metal-coated polyester mesh, 2 - outer frame, 3 - sealing tape, 4 - light source. Specific implementation method:

[0029] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0030] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0031] Embodiment 1:

[0032] like Figure 1 As shown, a composite glass stone material is composed of a stone part 1 and an outer frame 2 arranged outside the stone part. A sealing belt 3 is arranged at the cross section of the stone part 1, and a light source 4 is arranged inside the outer frame 2.

[0033] The stone part 1 comprises stone 11, adhesive layer 12, glass 13, adhesive layer 12 and stone 11 from top to bottom, the stone 11 has a thickness of 1-2 mm, the adhesive layer 12 is a TPU film, the thickness of the adhesive layer 12 is 50 μm, the glass 13 is a laser engraved and dotted float glass, the thickness of the glass 13 is 4 mm; the sealing tape 3 is an aviation-grade waterproof and weather-resistant TPU hot-melt tape, the thickness of the sealing tape 3 is 25 μm; the outer frame 2 is a stainless steel frame; the light source 4 is an LED light source.

[0034] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0035] 1) Stone preparation: Cut and grind the base stone into 2mm thick and 3000mm*2000mm size stone; it can be cut into any size; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass 13 and stone 11 to remove surface dirt and impurities; 3) Pretreatment: Place the glass 13, adhesive layer 12, and stone 11 in a constant temperature and humidity environment for 60 hours, the ambient temperature is 18°C, and the ambient humidity is 10%; 4) Stone bonding: Place the pretreated stone 11, adhesive layer 12, glass 13, adhesive layer 12, and stone 11 in the order from top to bottom. The semi-finished composite glass stone material is placed in sequence, and sealing tapes 3 are placed on the sections around it. The laminating chamber is evacuated to 1 atmosphere, and the temperature of the laminating chamber is raised to 135°C and maintained for 60 minutes before the semi-finished composite glass stone material is taken out; 5) Post-laminating shaping: a mixed solvent of alcohol and acetone is used to wipe off the adhesive layer 12 overflowing from the semi-finished composite glass stone material during laminating and the residual glue of the sealing tape 3, and the semi-finished composite glass stone material is reheated at a heating temperature of 130°C for 25 minutes; 6) External frame installation: the light source 4 is installed in the external frame 2, and the external frame 2 is installed on the outside of the sealing tape 3 to obtain a finished composite glass stone material.

[0036] Embodiment 2:

[0037] like Figure 2 As shown, a composite glass stone material is composed of a stone part 1 and an outer frame 2 arranged outside the stone part. A sealing belt 3 is arranged at the cross section of the stone part 1, and a light source 4 is arranged inside the outer frame 2.

[0038] The stone part comprises glass 13, adhesive layer 12 and stone 11 from top to bottom, the thickness of the stone 11 is 3 mm, the adhesive layer 12 is a PVB film, the thickness of the adhesive layer 12 is 50 μm, the glass 13 is a laser engraved and dotted PMMA plate, the thickness of the glass 13 is 5 mm; the sealing tape 3 is an aviation-grade GS hot-melt tape, the thickness of the sealing tape 3 is 25 μm; the outer frame is an aluminum profile frame; the light source is an LED light source.

[0039] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0040] 1) Stone preparation: Cut and grind the base stone into 3mm thick and 3000mm*2000mm size stones; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass 13 and stone 11 to remove dirt and impurities on the surface; 3) Pretreatment: Place the glass 13, adhesive layer 12, and stone 11 in a constant temperature and humidity environment for 48 hours, the ambient temperature is 16°C, and the ambient humidity is 12%; 4) Stone bonding: Place the pretreated glass 13, adhesive layer 12, and stone 11 in order from top to bottom, and Place the sealing tape 3, evacuate the laminating chamber to 1 atmosphere, and heat the laminating chamber to 135-150°C for 50-70 minutes before taking out the composite glass stone semi-finished product; 5) Post-laminating shaping: use a mixed solvent of alcohol and acetone to wipe off the adhesive layer 12 overflowing from the composite glass stone semi-finished product during laminating and the residual glue of the sealing tape 3, and reheat the composite glass stone semi-finished product at a heating temperature of 135°C for 20 minutes; 6) External frame installation: install the light source 4 in the external frame 2, and then install the external frame 2 on the outside of the sealing tape 3 to obtain a composite glass stone finished product.

[0041] Embodiment 3:

[0042] like Figure 3 As shown, a composite glass stone material is composed of a stone part 1 and an outer frame 2 arranged outside the stone part 1, a sealing belt 3 is arranged at the cross section of the stone part 1, and a light source 4 is arranged inside the outer frame 2.

[0043] The stone part comprises glass 13, adhesive layer 12, stone 11, adhesive layer 12 and glass 13 from top to bottom, the stone 11 is 2 mm thick, the adhesive layer 12 is a TPU film, the adhesive layer 12 is 60 μm thick, the top glass 13 is tempered glass, the bottom glass 13 is a laser engraved PMMA plate, and the glass 13 is 5 mm thick; the sealing tape is an aviation-grade waterproof and weather-resistant GS hot-melt tape, and the thickness of the sealing tape is 20 μm; the outer frame 2 is an aluminum profile frame; the light source 4 is an LED light source.

[0044] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0045] 1) Stone preparation: Cut and grind the base stone into 2mm thick and 3000mm*2000mm size stone; it can be cut to any size; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass 13 and stone 11 to remove dirt and impurities on the surface; 3) Pretreatment: Place the glass 13, adhesive layer 12, and stone 11 in a constant temperature and humidity environment for 60 hours, the ambient temperature is 20℃, and the ambient humidity is 12%; 4) Stone bonding: Place the pretreated glass 13, adhesive layer 12, stone 11, adhesive layer 12, and glass 13 from top to bottom The laminating chamber is evacuated to 1 atmosphere, and the temperature of the laminating chamber is raised to 140°C for 50 to 70 minutes before the composite glass stone semi-finished product is taken out; 5) Post-lamination shaping: a mixed solvent of alcohol and acetone is used to wipe off the adhesive layer overflowed from the composite glass stone semi-finished product during lamination and the residual glue of the sealing tape, and the composite glass stone semi-finished product is reheated at a heating temperature of 140°C for 25 minutes; 6) External frame installation: the light source is installed in the external frame, and the external frame is installed on the outside of the sealing tape to obtain a composite glass stone finished product.

[0046] Embodiment 4:

[0047] like Figure 4 As shown, a composite glass stone material is composed of a stone part 1 and an outer frame 2 arranged outside the stone part 1, a sealing belt 3 is arranged at the cross section of the stone part 1, and a light source 4 is arranged inside the outer frame 2.

[0048] The stone part 1 comprises glass 13, adhesive layer 12, stone 11, adhesive layer 12 and glass 13 from top to bottom, the thickness of the stone 11 is 3 mm, the adhesive layer 12 is GS film, the thickness of the adhesive layer 12 is 40 μm, the top glass 13 is laser engraved and dotted glass, the bottom glass 13 is PMMA board, the thickness of the glass is 5 mm, and the two adhesive layers 12 form a closed loop; the sealing tape is aviation-grade waterproof and weather-resistant GS hot-melt tape, the thickness of the sealing tape is 30 μm; the outer frame is a PVC frame; the light source is an LED light source.

[0049] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0050] 1) Stone preparation: Cut and grind the base stone to 3mm thickness and 3000mm*2000mm size; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass 13 and stone 11 to remove dirt and impurities on the surface; 3) Pretreatment: Place the glass 13, adhesive layer 12, and stone 11 in a constant temperature and humidity environment for 60 hours, the ambient temperature is 20℃, and the ambient humidity is 10%; 4) Stone bonding: Place the pretreated glass 13, adhesive layer 12, stone 11, adhesive layer 12 and glass 13, and the stone 11 in the order from top to bottom. The semi-finished composite glass stone material is placed in sequence, and sealing tapes 3 are placed on the sections around it. The laminating chamber is evacuated to 1 atmosphere, and the temperature of the laminating chamber is raised to 140°C and maintained for 60 minutes before the semi-finished composite glass stone material is taken out; 5) Post-laminating shaping: a mixed solvent of alcohol and acetone is used to wipe off the adhesive layer 12 overflowing from the semi-finished composite glass stone material during laminating and the residual glue of the sealing tape 3, and the semi-finished composite glass stone material is reheated at a heating temperature of 140°C for 25 minutes; 6) External frame installation: the light source 4 is installed in the external frame 2, and the external frame 2 is installed on the outside of the sealing tape 3 to obtain a finished composite glass stone material.

[0051] Embodiment 5:

[0052] like Figure 5 As shown, a composite glass stone material is composed of a stone part 1 and an outer frame 2 arranged outside the stone part 1, a sealing belt 3 is arranged at the cross section of the stone part 1, and a light source 4 is arranged inside the outer frame 2.

[0053] The stone part comprises glass 13, adhesive layer 12, metal-coated polyester mesh 14, adhesive layer 12 and glass 13 from top to bottom. The metal-coated polyester mesh 14 has a wire diameter of 140-500um and a light transmittance of 25-60%. The adhesive layer 12 is an SGP film with a thickness of 196μm. The top glass 13 is laser engraved and dotted tempered glass, the bottom glass 13 is tempered glass, and the thickness of the glass 13 is 4-20mm. The sealing tape 3 is an aviation-grade waterproof and weather-resistant GS hot-melt tape with a thickness of 35μm. The outer frame 2 is a PVC frame. The light source is an LED light source.

[0054] A method for preparing a composite glass stone material, characterized in that it comprises the following steps:

[0055] 1) Material preparation: Cut the base metal-coated polyester mesh 14 into 140-500um thickness and 5000mm*1600mm size; it can be cut to any size; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass 13 and the metal-coated polyester mesh 14 to remove dirt and impurities on the surface; 3) Pretreatment: Place the glass 13, adhesive layer 12, and metal-coated polyester mesh 14 in a constant temperature and humidity environment for 50 hours, the ambient temperature is 18°C, and the ambient humidity is 10%; 4) Stone bonding: Place the pretreated glass 13, adhesive layer 12, metal-coated polyester mesh 14, and adhesive layer 1 2 and glass 13 are placed in order from top to bottom, and sealing tape 3 is placed at the sections around them, the laminating chamber is evacuated to 1 atmosphere, and the laminating chamber is heated to 140°C and maintained for 60 minutes before taking out the composite glass stone semi-finished product; 5) Post-lamination shaping: a mixed solvent of alcohol and acetone is used to wipe off the adhesive layer 12 and the residual glue of the sealing tape 3 that overflowed from the composite glass stone semi-finished product during lamination, and the composite glass stone semi-finished product is reheated at a heating temperature of 140°C for 25 minutes; 6) Outer frame installation: the light source 4 is installed in the outer frame 2, and the outer frame 2 is installed on the outside of the sealing tape 3 to obtain a composite glass stone finished product.

[0056] The composite glass stone of the present invention is provided with a sealing tape 3 at the cross section, which can effectively prevent the adhesive layer 12 and the metal-coated polyester mesh 14 from decreasing in viscosity after absorbing water; the provision of the outer frame 2 and the light source 4 is helpful for the image display of the glass; in the process of bonding the composite glass stone, the present invention removes moisture and bubbles in the glass 13, the adhesive layer 12, the stone 11 and the metal-coated polyester mesh 14 through pretreatment, which can ensure that the composite glass stone is bonded more firmly; and then through bonding and shaping, the overflow glue generated during bonding is removed, and the bubbles in the adhesive layer 12 and the sealing tape 3 are further removed, so as to ensure the bonding strength and decorative beauty of the composite stone.

[0057] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is obvious that many changes and variations can be made in accordance with the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes.

Claims

1. A composite glass stone, characterized in that: The composite glass stone is composed of a stone part and an outer frame arranged on the periphery of the stone part, a sealing belt is arranged at the cross section of the stone part, and a light source is arranged in the outer frame; the stone part is composed of glass, an adhesive layer, a metal-coated polyester mesh, an adhesive layer and glass from top to bottom, the thickness of the polyester mesh is 1-5mm, the adhesive layer is a GS film, an EVA film, a PVB film, a TPU film or an SGP film, the thickness of the adhesive layer is 20-100μm, the glass is float glass, tempered glass, PMMA board, PC board, PETG board, PET board, and the thickness of the glass is 1-25mm.

2. The composite glass stone according to claim 1, characterized in that: The sealing tape is aviation-grade waterproof and weather-resistant GS hot-melt tape, PEN hot-melt tape, PES hot-melt tape, PA hot-melt tape, TPU hot-melt tape or PO hot-melt tape, and the thickness of the sealing tape is 5-50 μm.

3. The composite glass stone according to claim 1, characterized in that: The outer frame is a stainless steel frame, an aluminum profile frame, a PVC frame or an ABS frame.

4. The composite glass stone according to claim 1, characterized in that: The light source is an LED light source.

5. A method for preparing a composite glass stone, characterized in that: The composite glass stone is composed of a stone part and an outer frame arranged on the periphery of the stone part, a sealing belt is arranged at the cross section of the stone part, and a light source is arranged in the outer frame; the stone part is composed of glass, an adhesive layer, a metal-coated polyester mesh cloth, an adhesive layer and glass from top to bottom, the wire diameter of the metal-coated polyester mesh cloth is 140-500 μm, and the light transmittance is 25-60%, the adhesive layer is an SGP film, the thickness of the adhesive layer is 196 μm, the top layer of glass is laser engraved and dotted tempered glass, the bottom layer of glass is tempered glass, and the thickness of the glass is 4-20 mm; the sealing belt is an aviation-grade waterproof and weather-resistant GS hot-melt tape, and the thickness of the sealing belt is 35 μm; The outer frame is a PVC frame; the light source is an LED light source; The preparation method comprises the following steps: 1) Material preparation: Cut the base metal coated polyester mesh into 140-500um thickness and 5000mm*1600mm size; 2) Cleaning: Use an ultrasonic cleaning machine with plasma water to clean the glass and metal-coated polyester mesh to remove dirt and impurities on the surface; 3) Pretreatment: Place the glass, adhesive layer, and metal-coated polyester mesh in a constant temperature and humidity environment for 50 hours, wherein the ambient temperature is 18° C. and the ambient humidity is 10%; 4) Stone bonding: Place the pre-treated glass, adhesive layer, metal-coated polyester mesh, adhesive layer and glass in order from top to bottom, and place sealing tapes on the sections around them. Evacuate the bonding chamber to 1 atmosphere, and heat the bonding chamber to 140°C for 60 minutes before taking out the composite glass stone semi-finished product. 5) Post-pasting shaping: Use a mixed solvent of alcohol and acetone to wipe off the adhesive layer and residual adhesive of the sealing tape that overflowed from the composite glass stone semi-finished product during the pasting, and reheat the composite glass stone semi-finished product at a heating temperature of 140°C for 25 minutes; 6) Installation of outer frame: install the light source in the outer frame, and then install the outer frame on the outside of the sealing belt to obtain a composite glass stone finished product.